Penanaman nilai kearifan lokal pada anak usia dini di TK Negeri 3 Suryoputran kota yogyakarta - Dyaloka Puspita Ningrum (Jurnal Komunikasi Profesional, 2020)
The abundance of information flow in the modern era has brought a very big impact on human life. The entry of foreign cultures as a result of the globalization process can threaten the nation's cultural characteristics and values, including in the city of Yogyakarta. The culture in Yogyakarta City holds charm with local wisdom values, such as traditional dances, traditional music, traditional games, petitahs, regional motto/pantun, regional art performances, traditional culinary delights, folklore and so forth. But now people tend to understand the culture and appreciate it only on national holidays or certain celebrations. Thus it is very necessary to instil national values, especially in young children in TK Negeri 3 Suryoputran, Yogyakarta City using the method of reflection, discussion and simulation. It is hoped that innocent young children can practice and learn a regional culture in the midst of the widespread use of gadgets given by parents to children in the midst of their busy lives.